1973
DOI: 10.1111/j.1537-2995.1973.tb04468.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Latham Blood Processor To Perform Plateletpheresis

Abstract: Platelets were separated during extracorporeal circulation by the method of Tulliir ct aZ. in the Latham Blood Processor equipped with a 375 ml disposable centrifuge bowl. The average yield of platelets recovered from each 710 ml unit of blood was 0.665 X 1011 2 0.244 X 1011 ( 2 1 S. D.) N =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…A previous report [4] has indicated that the average number of platelets recovered from a discontinuous flow centrifugation procedure exceeded by almost two fold the average decrease in the total quantity of circulating platelets. It was suggested that there was mobilization from the platelet pool during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report [4] has indicated that the average number of platelets recovered from a discontinuous flow centrifugation procedure exceeded by almost two fold the average decrease in the total quantity of circulating platelets. It was suggested that there was mobilization from the platelet pool during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The platelets collected with the Fenwal CS-3000 had low leukocyte counts; leukocytepoor platelets are recommended for patients requiring repeated platelet transfusions [1,4], It should be noted that the IBM Blood Processor now can be operated with a dual stage channel to collect a leukocyte-poor platelet concentrate, with a platelet yield comparable to that achieved with the Fen wal CS-3000 [6], During plateletpheresis, platelets are mo bilized, probably from the splenic storage pool, into the vascular space [7][8][9][10], An un expected finding from this study was that donors plateletpheresed with the IBM Blood Processor 2997 (31%) exhibited a signifi cantly lower platelet count after collection than donors plateletpheresed with the Haemonetics Blood Processor 30 (18%) or the Fenwal CS-3000 (19%). The number of platelets isolated with the IBM Blood Pro cessor 2997 was similar to the Haemonetics Blood Processor 30, and the IBM Blood Pro cessor 2997 and the Fenwal CS-3000 had similar collection times.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has not been shown that infu sion of HES into healthy blood donors re pheresis [21], and probably reflect changes in blood volume caused by the supine position [24], infusion of intravenous fluids and phys ical removal of platelets. The peripheral WBC count increased significantly as a re sult of the procedure (table I).…”
Section: Discussionmentioning
confidence: 99%
“…Calculations Liters of blood processed (LBP) was calculated with the following formula [21]: WBC Harvesting The contents of bag No. 1 (HES and cells) and of the bowl (WBC-rich RBC) were directed into bag No.…”
Section: Laboratory Testsmentioning
confidence: 99%